MODELING AND LOGIC OF DECISION-MAKING WHEN FORMING THE TRADITIONAL CHARACTER OF THE HISTORICAL ENVIRONMENT OF ODESSA CATHEDRAL SQUARE, UKRAINE - Мещеряков, Владимир (SWorldJournal, 2020)
The paper examines the possibility of using scientific and practical methods in the formation of the traditional character of the historical environment of the Cathedral Square in Odessa, Ukraine, with the reconstruction of an outstanding lost object of